Updated taxonomy of Chinese Cantharellus subgenera Afrocantharellus and Magni (Hydnaceae, Cantharellales): Three new taxa and amended descriptions of one previous species - Zhang, Yu-Zhuo; Qin, Hua-Zhi; Chen, Zuo-Hong; Lin, Wen-Fei; Liang, Zhi-Qun; Jiang, Shuai; Zeng, Nian-Kai (Frontiers in Microbiology, 2023)
Cantharellus, one of the main genera of Hydnaceae (Cantharellales), is both ecologically and economically important. Although many studies have focused on this genus in China, the taxonomy should be further updated. In the present study, Cantharellus subgenera Afrocantharellus and Magni were investigated based on morphology and molecular phylogenetic analyses with new collections from China. Five phylogenetic species were recognized among the studied collections, three of which were described as new: C. bellus, C. cineraceus, and C. laevigatus; one was previously described taxon: C. hygrophoroides; and the remaining species was not defined due to the paucity of the materials. Among the four described species, both C. bellus and C. laevigatus are members of subgen. Magni, whereas C. cineraceus and C. hygrophoroides belong to subgen. Afrocantharellus.